Influence of the WHO framework convention on tobacco control on tobacco legislation and policies in sub-Saharan Africa (2018)
"Background: The World Health Organization’s Framework Convention on Tobacco Control, enforced in 2005, was a watershed international treaty that stipulated requirements for signatories to govern the production, sale, distribution, advertisement, and taxation of tobacco to reduce its impact on health. This paper describes the timelines, context, key actors, and strategies in the development and implementation of the treaty and describes how six sub-Saharan countries responded to its call for action on tobacco control. Methods: A multi-country policy review using case study design was conducted in Cameroon, Kenya, Nigeria, Malawi, South Africa, and Togo. All documents related to the WHO Framework Convention on Tobacco Control and individual country implementation of tobacco policies were reviewed, and key informant interviews related to the countries’ development and implementation of tobacco policies were conducted. Results: Multiple stakeholders, including academics and activists, led a concerted effort for more than 10 years to push the WHO treaty forward despite counter-marketing from the tobacco industry. Once the treaty was enacted, Cameroon, Kenya, Nigeria, Malawi, South Africa, and Togo responded in unique ways to implement tobacco policies, with differences associated with the country’s socio-economic context, priorities of country leaders, industry presence, and choice of strategies. All the study countries except Malawi have acceded to and ratified the WHO tobacco treaty and implemented tobacco control policy. Conclusions: The WHO Framework Convention on Tobacco Control provided an unprecedented opportunity for global action against the public health effects of tobacco including non-communicable diseases. Reviewing how six sub-Saharan countries responded to the treaty to mobilize resources and implement tobacco control policies has provided insight for how to utilise international regulations and commitments to accelerate policy impact on the prevention of non-communicable diseases."